WHY DOES MINING DEVELOPMENT PRODUCE INFORMAL SETTLEMENTS? AN INVESTIGATION FROM A POLICY PERSPECTIVE - Mr Luyolo Bosman (IJRDO - Journal of Social Science and Humanities Research, 2025)
Mining development has historically played a pivotal role in shaping the socio-economic and spatial landscape of South Africa. While contributing significantly to national GDP and employment, it has also engendered the proliferation of informal settlements adjacent to mining sites. This paper investigated the relationship between mining expansion and informal settlement formation through a policy-oriented lens, with specific attention to governance dynamics, institutional fragmentation, and spatial injustice. Employing a mixed-methods approach comprising qualitative interviews, spatial policy analysis, and documentary review, the study interrogated how legislative gaps and institutional silos perpetuate marginality in mining zones. The findings revealed that informal settlements were not merely spontaneous or illegal responses to urban migration but were deeply rooted in the failure of integrated planning frameworks, limited community participation, and inconsistent implementation of mining social responsibility obligations. The research identified structural misalignments between municipal, provincial, and national planning bodies, which contributed to a policy vacuum exploited by unregulated urbanisation. Furthermore, mining companies’ compliance with social and labour plans was found to be inconsistent, exacerbating service delivery deficits and socio-economic exclusion. Drawing on spatial justice theory and the principles of inclusive governance, the paper advocates for a recalibration of urban policy to formally recognise informal settlements as legitimate urban spaces and to embed collaborative governance strategies that involve affected communities, industry, and the state. This study contributes to the discourse on sustainable urban transformation by offering actionable policy recommendations for addressing entrenched inequality in post-apartheid urban peripheries.